Influence of Sticky Rice and Jaggery Sugar Addition on Lime Mortar - Mydin, M. A. O. (Engineering, Technology & Applied Science Research, 2022)
Lime mortar has many advantages, yet its durability properties are the most remarkable, making it very useful in building preservation. Traditional mortar for conservation and restoration work contains lime, which guarantees that the fresh mortar is applied to the underlying layer, increases its setting time, and gives adequate workability. This research aims to determine the durability performance, mechanical properties, and optimum percentage of organic admixtures to be used in lime mortar. Five mix proportions and one control lime mortar mix were prepared. Mixes with jaggery sugar and sticky rice with weight proportions of 3%, 6%, 9%, 12%, and 15% were compared with the control lime mortar mix. The results show that 9% sticky rice lime mortar achieved the highest performance in terms of mechanical and durability properties.